Investigating the Prospect of C-Type Lectin-like Receptors-2 for Predicting Prognosis of Ischemic Stroke: Rapid Review of Molecular Mechanisms to Clinical Study - Rayhan Farandy; Muhammad Ilham Dhiya Rakasiwi; Muhammad Zaki Bariz Amaanullah; Nurul Gusti Khatimah (Majalah Biomorfologi, 2025)
Highlights The potential of CLEC-2 as a prognostic biomarker for ischemic stroke is supported by in vivo and clinical studies demonstrating its role in thrombo-inflammatory mechanisms and clinical outcome prediction. Analysis of clinical studies indicates that elevated plasma CLEC-2 levels are associated with an increased risk of recurrent vascular events and mortality in acute ischemic stroke, suggesting its promise as a noninvasive tool for stroke prognosis assessment.   ABSTRACT Background: Every year, over 13.7 million individuals experience strokes, resulting in approximately 5.8 million deaths. C-type lectin-like receptor 2 (CLEC-2) plays a significant role in platelet activation, which is elevated in ischemic stroke and is associated with disease progression and prognosis. Objective: To review the literature on the potential of CLEC-2 as a biomarker for assessing the prognosis and progression of ischemic stroke. Material and Method: This rapid review followed the Cochrane interim guidelines and adhered to PRISMA standards. A comprehensive search was conducted in PubMed, Cochrane Library, and Google Scholar to identify original research articles published in English over the past 10 years. Studies at various stages—including in vitro, in vivo, and clinical trials—were included if they evaluated the association between CLEC-2 and acute ischemic stroke. Risk of bias was assessed using the QUIPS tool for clinical studies and SYRCLE’s tool for animal studies. Study selection and data extraction were performed independently by three reviewers. Result: The search identified five relevant articles: two experimental studies and three clinical prognostic studies examining CLEC-2 in the context of ischemic stroke. CLEC-2, a receptor for podoplanin expressed in various tumors and lymphatic endothelial cells, induces a calcium surge independent of secondary platelet activation. In vivo studies have demonstrated increased levels of CLEC-2 and podoplanin, which are highly expressed on neurons and microglia in ischemic brain regions. The three clinical studies showed that plasma CLEC-2 levels have prognostic value in predicting recurrent vascular events and mortality in patients with acute ischemic stroke. Conclusion: Plasma CLEC-2 shows potential as a biomarker for evaluating the progression and prognosis of acute ischemic stroke.